The relationship between organizational commitment and turnover intention among temporary employees in the local government: Mediating role of perceived insider status and moderating role of gender - Xia, Defeng; Sun, Jingru; Zhang, Congcong; Zhang, Yiying (Frontiers in Psychology, 2022)
The purpose of this study is to examine the relationships between organizational commitment and turnover intention, and to test the mediating effect of perceived insider status, and moderating effect of gender on that relationship. Data were collected using a questionnaire survey method from 820 temporary employees of government agencies working in China. The data obtained were analyzed according to the moderated mediation. As a result of the analysis, it was determined that perceived insider status has a partial mediation effect on the relationship between organizational commitment and turnover intention. Also, the results supported the moderated mediation and showed that the indirect effect of organizational commitment and turnover intention through perceived insider status was weaker for males than females. Then, the theoretical and practical implications of the findings are discussed.